The Prevalence of Corruption in Pakistan's Judicial and Law Enforcement Sectors - Imran, Muhammad; Murtiza, Ghulam; Tariq, Khalil-ur-Rehman (Pakistan Languages and Humanities Review, 2023)
This paper investigates the prevalence of corruption in Pakistan's judicial and law enforcement sectors. In Pakistan, corruption has been a pervasive issue for decades, with negative effects on the economy and society as a whole. Corruption in the judicial and law enforcement sectors is of particular concern as it has far-reaching consequences for the rule of law and public trust in the justice system. It uses a mixed-method approach. The research design includes surveys and interviews with relevant stakeholders, including judges, lawyers, police officers, and ordinary citizens. The sample size is determined using a stratified random sampling technique, and the data is analyzed using both qualitative and quantitative methods. The study's results provide a compelling case for urgent reforms to combat corruption in Pakistan's justice system. This paper suggests that accountability, transparency, and public awareness in promoting the rule of law and social justice.